Neurochemistry: cellular, molecular, and clinical aspects - Teelken, Albert; Korf, Jaap (Springer, 1997)
Proceedings of the 11th European Society for Neurochemistry Meeting held in Groningen, The Netherlandes, June 15-20, 1996.